MEMPOSISIKAN KEMBALI KUASA PEREMPUAN DALAM PERDAMAIAN HUBUNGAN ANTARAGAMA (Kasus di Kelurahan Klitren, Kecamatan Gondokusuman, Yogyakarta) - Siantari Rihartono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
At issue is that it involves the issue of women, may be one solution, which has barely taken into account in each of the steps in building peace among religious believers . Conflict is always synonymous with the male role, so it must be dealt with men . Whereas in some political facts it appears that women are behind men, often have a very central position in decision-making by men.This study examines three key issues, namely the portrait of life among religious women, women’s strategies to prevent and keep the peace, and how the power of women in peace building creates. Such a study is important, because during the public often view a woman’s face as the face of oppression. This is a qualitative study, using observation and participation, also conducted in-depth interviews with several groups. Direct involvement of the researcher in the study site, is able to determine the key informants (key informants ) to be involved in in-depth interviews to issues the position of women in family, social, and culture in the context of their ability to make efforts for peace.From the research result, that the activities of women over the cultural nature, it becomes a crutch and a major force in the process of creating and maintaining peace among religious believers, so that they can become the main pillar of the movements of the peace and harmony of creation which was pioneered by men.